Microwave Vacuum Drying Characteristics of Noni Fruits (Morinda Citrifolia L.) and Their Effects on Scopoletin Content - Asr, Mina Habibi (2009)
The main objective of this study was to investigate microwave-vacuum drying characteristics of Morinda citrifolia fruit slices and drying effects on Scopoletin content. A laboratory microwave-vacuum dryer was designed and fabricated and preliminary tests were conducted to ensure that its operation is satisfactory. M.citrifolia fruit slices were dried under different drying techniques such as: microwave-vacuum drying, microwave drying (without applying vacuum) and sun drying. Microwave-vacuum drying of M.citrifolia fruit slices were carried out at three levels of microwave power; 180, 300 and 450W and four levels of absolute pressure; 91 kPa, 86 kPa, 71 kPa and 41 kPa, whilst, microwave drying was conducted at atmospheric pressure (101 kPa). Drying was performed in two microwave application namely pulsed and continuous. In pulsed microwave drying mode, the magnetron was alternatively switched on and off in order to achieve desired pulsing ratio. The magnetron was switched on for 30 s and switched off for 150 s, corresponding to selected pulsing ratio of 6. M.citrifolia fruit slices having initial moisture content of about 5-6 g water/ g dry matter were dried to final moisture content of approximately 0.5 g water/ g dry matter within 10 to 252 min depending on microwave power, vacuum condition and microwave heating mode. For continuous microwave heating mode, the drying time was within 5 to 45 min, while for pulsed microwave heating mode it was within 33 to 198 min. Higher microwave power level and lower pressure increased the drying rate. The result shows that even though pulsed microwave heating mode was more time consuming overall, but total power-on time was about the same as continuous microwave heating mode; however, in pulsed microwave heating mode drying took place at lower product temperature. Page equation was most satisfactory to describe thin-layer drying characteristic of M.citrifolia fruit slices among the three tested thin-layer drying equations, with lower reduced chi-square X2 and RMSE and higher value for R2. Scopoletin was extracted from fresh and dried sample by solvent method using methanol and spectrofluorometric method was used for its determination. The Scopoletin content retention of M. citrifolia fruit slices dried under different drying techniques was evaluated and was found to be within 5 to 53%. In pulsed microwave heating mode, drying at atmospheric pressure resulted in higher Scopoletin content reduction with microwave power set at 450 W power level (20%); however, in continuous microwave heating mode at the atmospheric pressure, the lowest microwave power of 180W resulted in higher Scopoletin content reduction (51%). The reason for this, is due to longer drying time required at lower microwave power level, and higher temperature achieved due to longer power-on time during continuous microwave heating mode compared to pulsed microwave heating mode.